Fabrication and Characterization of Cement-Based Hybrid Concrete Containing Coir Fiber for Advancing Concrete Construction - Herda Yati Binti Katman; Wong Jee Khai; Naraindas Bheel; Mehmet Serkan Kırgız; Aneel Kumar; Omrane Benjeddou (Buildings, 2022)
Nowadays, the incorporation of natural fiber, such as coir fiber, to high-strength concrete has sparked a lot of attention in the construction materials industry. This is because coir fibers are significantly cheaper and more widely accessible than synthetic fibers. Natural fibers such as bamboo, flax, hemp, and coir have distinct microstructures and chemical compositions from cement-based materials. The physical and mechanical properties of natural fiber, such as coir fiber, are significantly correlated with fiber concentration and cellulose component. However, coir fiber has high stretching to failure, while bamboo, flax, and hemp fibers are very resistant to stress and increase stiffness. Based on these distinctive fiber qualities, it is anticipated that coir fiber would facilitate the development of cement-based materials for advanced concrete building applications. In this paper, coir fiber-reinforced cement-based concretes were evaluated in terms of workability, compressive strength, flexural strength, splitting tensile strength, modulus of elasticity, and permeability. The relationship between strength and fiber content was analyzed to understand the impact of coir fiber on the properties of coir fiber-reinforced cement-based concrete. Based on the results obtained, it is determined that 2% coir fiber modification offers the highest compressive strength, splitting tensile strength, and flexural strength. Moreover, the modulus of elasticity is increased, and the permeability is plummeted by the volume fractions of coir fiber 1%, 2%, and 3% because the blending of coir fiber has a bridging and dispersing mechanism of the force-carrying capacity in concrete. In conclusion, coir fiber might be a viable choice for improving the strength and durability of concrete. Therefore, the sparing use of coir fiber presented in this research can be implemented for the manufacturing of concrete in the future.